Exploring Educational Equity: New Insights from TIMSS and National Achievement Metrics in Tunisia - Abdaoui, Noura; Brahim, Ahmat; Ahmed, Tasabeeh; Prihatin, Laela Tri; Akpo, Simon Eno (jurnal matematika, 2024)
Purpose of the study: This paper investigates the relationship between mathematics achievement in the Trends in Mathematics and Science Study (TIMSS) and two key school achievement measures—grades and national test results—in Tunisia. Going beyond previous studies, this research also explores how these relationships differ across diverse student subgroups, providing a nuanced understanding of educational equity. Methodology:Give name, Employing robust statistical analyses, the study uncovers a strong positive correlation between TIMSS mathematics scores and both grade 6 and grade 9 achievement measures, underscoring TIMSS’s reliability as an indicator of student performance in the national context. Notably, students from more educated households consistently outperformed their peers from less-educated backgrounds on TIMSS, and the association between TIMSS scores and school achievement measures was significantly stronger for students from advantaged home environments. Main Findings: These findings suggest that socioeconomic factors and school contexts critically shape TIMSS performance, highlighting disparities in educational outcomes. Furthermore, the results call for a re-evaluation of how TIMSS data is interpreted and utilized in national education policies, especially in addressing inequities. By illuminating the complex interplay between individual backgrounds, school contexts, and standardized assessments, this study contributes to a deeper understanding of TIMSS as both a tool for measuring student achievement and a reflection of systemic challenges. Novelty/Originality of this study: These insights have profound implications for policymakers, educators, and researchers seeking to leverage TIMSS data for meaningful educational improvements while ensuring equity across diverse student populations.